Association between non-high-density lipoprotein cholesterol-to-high-density lipoprotein cholesterol ratio and macroalbuminuria: evidence from NHANES 1999-2018 - Huang, Dongli; He, Yuan (Frontiers in Endocrinology, 2025)
PurposeThe non-high-density lipoprotein cholesterol to high-density lipoprotein cholesterol ratio (NHHR) is a crucial lipid marker associated with various cardiovascular diseases. However, its relationship with kidney injury, particularly albuminuria, remains poorly understood. This study aims to investigate the association between NHHR and macroalbuminuria in U.S. adultsPatients and methodsThis cross-sectional study utilized data from the 1999–2018 National Health and Nutrition Examination Survey (NHANES). NHHR was calculated as (Total cholesterol - HDL cholesterol)/HDL cholesterol. Macroalbuminuria was defined by an albumin-creatinine ratio (ACR) >300 mg/g. Logistic regression, smoothed curve fitting, subgroup analyses, and sensitivity analysis were employed to assess the relationship between NHHR and macroalbuminuria.ResultsA total of 41,225 participants were included in the analysis. Higher NHHR was significantly associated with an increased likelihood of macroalbuminuria (OR = 1.34, 95% CI: 1.13–1.59, p=0.0007). Subgroup analysis revealed a stronger association in participants with BMI ≥30 kg/m2(OR = 1.89, 95% CI: 1.44–2.47, p<0.01). Sensitivity analysis revealed that the association remained robust even after excluding participants taking medications that affect lipid metabolism.ConclusionIn U.S. adults, an increased likelihood of incident NHHR levels of macroalbuminuria is positively associated and is more pronounced in those with a BMI ≥30kg/m2.